2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4650232
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of a full-body inertial motion capture system for clinical gait analysis

Abstract: In order for gait analysis to be established as part of routine clinical diagnoses, an accurate, flexible and user-friendly motion capture system is required. Commonly used optical, mechanical and acoustic systems offer acceptable accuracy and repeatability, but are often expensive and restricted to laboratory use. Inertial motion capture has seen great innovation in the last few years, but the technology is not yet considered mature enough for clinical gait analysis. In this paper we compare the kinematic rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 8 publications
2
94
0
1
Order By: Relevance
“…In order to perform a standardized clinical gait analysis (M1) the evaluated MVN suit (XSens) [25,26] has been applied. During the test, all subjects walked for 5 min on a level hallway up and down (walking distance: 20 m; analyzed: 16 m).…”
Section: Methodsmentioning
confidence: 99%
“…In order to perform a standardized clinical gait analysis (M1) the evaluated MVN suit (XSens) [25,26] has been applied. During the test, all subjects walked for 5 min on a level hallway up and down (walking distance: 20 m; analyzed: 16 m).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the study reports good accuracy in hip angle tracking compared to a gold-standard optical system. Another study comparing Vicon joint angles to the Xsens biomechanical model outputs found similar results, with sagittal plane values being highly correlated and transverse and coronal plane angles being mildly correlated [35]. The analysis investigated the intra-and inter-system differences in hip angle outputs for all three anatomical joint planes of motion due to STA and calibration poses.…”
Section: Discussionmentioning
confidence: 63%
“…Examples of their use in research studies include analysis of hip joint flexion and extension during human walking gait (Saber-Sheikh et al, 2010); assessment of spasticity assessment in children with Cerebral Palsy (Van den Noort, 2009); and measurement of lumber, hip, knee and ankle joint angles of skiers (Kondo et al, 2012). Cloete and Scheffer (2008) compared inertial motion capture of human gait kinematics against optical motion capture (n=8), demonstrating good reliability for hip and knee joint angle flexion.…”
Section: Introductionmentioning
confidence: 99%